The Role of Influencer Marketing in Digital Campaigns for Men's Skincare Health Products - Maulana, Muhamad Rifki; Purwanto, Eko; Fadli, Indra Miftahul (COMMUSTY Journal of Communication Studies and Society, 2025)
Recent advancements in healthcare technology have fueled the growth of Indonesia's skincare industry, particularly in men's skincare, reflecting evolving perceptions of masculinity. This study analyzes the role of influencer marketing in digital campaigns for men's skincare products, examining its impact on consumer perceptions, brand awareness, purchase intentions, and decisions.  Employing a qualitative literature review, this research examines scientific journals, articles, reports, books, and other relevant publications on influencer marketing, digital campaigns, and men's skincare consumer behavior.  Descriptive analysis focusing on key themes and findings from existing studies provides a comprehensive understanding of influencers' roles in shaping perceptions and purchase decisions through digital marketing strategies. This study addresses the gap in existing research by specifically focusing on the Indonesian men's skincare market and the unique role of influencer marketing within this context.  The findings contribute to a practical understanding of effective influencer marketing strategies within the digital communication and consumer behavior fields.